"I am making good money, but …": The precarious situation of Polish nurses in Norway. (29th May 2021) - Goździak, Elżbieta M.; Main, Izabella
Abstract: Precarity is defined as precarious existence, lacking in predictability, job security, material or psychological welfare. In migration studies, precarity is often associated with low wages, "illegality" and "deportability." Based on field research, this article focuses on Polish nurses working in Norway. As health professionals and citizens of the European Union, they do not possess the stereotypical characteristics of precarious workers. They are neither low skilled or poorly compensated nor unauthorised. Our findings emphasise multiple sources of Polish nurses' precarity in Poland – multiple low‐wage jobs, poor life‐work balance – and in Norway – short‐time assignments, variable working hours, high levels of mobility and challenges in family reunification. Precarity in Norway stemmed from policies that left recruitment of foreign‐born nurses in the hands of private agencies acting without an oversight of the Norwegian Health Directorate. Norway subscribes to the WHO ethical recruitment principles, but it falls short in monitoring private recruitment agencies.